Phytochemical and antibacterial potentials of Tecoma stans and Costus afer - Ini Patrick Ekpe; Esua Orok Udosen (International Journal of Phytomedicine, 2018)
Phytochemical composition and antibacterial potential of ethanolic extract of leaves/roots of Tecoma stans and leaves of Costus afer evaluated were collected at Malabo Campus, University of Calabar, Calabar and from Eman-Uruan local government area, Akwa Ibom, Nigeria respectively. Fresh leaves of both plants and roots of Tecoma stans collected were washed, dried on laboratory surface and milled into powder. They were separately extracted in 80% ethanol and the extracts concentrated in vacuo at 37-40oC to obtain semi solid dark green and brown concentrates respectively used for the evaluations. Phytochemical composition was determined using standard methods. The agar-well diffusion technique as described by Irobi et al, 1994 was employed for screening antibacterial activities. Five (5) bacterial isolates (Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsilla pneumoniae , P.speceis, Shigella sonnei, Morganella morganii,and Maraxella catarrhlis were obtained from the University of Calabar Teaching Hospital, Calabar. They were maintained on nutrient agar at 4oC in the refrigerator. The result showed that the leaves/roots of T.stans and leaves of C.afer contain Alkaloids, Flavonoids, Saponins and Glycosides. The MIC of leaves of T.stans showed 5.21mg/ml for S.aureus, 10.4mg/ml for E.coli, 83.3mg/ml for Proteus speies. The roots of T.stans showed 75mg/ml for S.aureus. The MIC for C.afer showed 5.2mg/ml for S. aureus and 312.5mg/ml for M. morganii. The results indicate that both plants can be used to achieve significant inhibitory effects as antimicrobial agents for treatment of bacterial infections in the absence of orthodox medication.